PENGARUH KUALITAS LAYANAN TERHADAP NIAT BELI ULANG KONSUMEN DI KAFE G'BOL DENGAN KEPUASAN SEBAGAI VARIABEL MODERASI (Studi Pada Kafe G'bol Jln. Sorowajan Baru No.16 Banguntapan, Bantul) - Eming Afiatna (MNJ 11 UMY 432, 2011)

(untitled)
This research having a purpose to know influence of service quality which consist of tangible, reliability, responsiveness, assurance and empathy to repurchasing intention. The sample collected using purposive sampling method. Responder in this research is consumer who which ever minimize twice purchasing product in G'bol cafe amounting to 100 people. Data obtained through primary data by sharing questionnaire to responder. Analyze data conducting by using double analysis regression, the hypothe